Microplastic pollution on the soil and its consequences on the nitrogen cycle: a review - Riveros, Gustavo; Urrutia, Homero; Araya, Juan; Zagal, Erick; Schoebitz, Mauricio (Environmental science and pollution research international, 2022)
Microplastics (MPs) correspond to plastics between 0.1 μm and 5 mm in diameter, and these can be intentionally manufactured to be microscopic or generated from the fragmentation of larger plastics. Currently, MP contamination is a complicated subject due to its accumulation in the environment. They are a novel surface and a source of nutrients in soils because MPs can serve as a substrate for the colonization of microorganisms. Its presence in soil triggers physical (stability of aggregates, soil bulk density, and water dynamics), chemical (nutrients availability, organic matter, and pH), and biological changes (microbial activity and soil fauna). All these changes alter organic matter degradation and biogeochemical cycles such as the nitrogen (N) cycle, which is a key predictor of ecological stability and management in the terrestrial ecosystem. This review aims to explore how MPs affect the N cycle in the soil, the techniques to detect it in soil, and their effects on the physicochemical and biological parameters, emphasizing the impact on the main bacterial groups, genes, and enzymes associated with the different stages of the N cycle.